Geochemistry and mineralogy of ochre-precipitates formed as waste products of passive mine water treatment - Valente, Teresa Maria Fernandes (2011)
Passive systems with constructed wetlands are designed to simulate natural attenuation processes in order to treat mine water in a long-term and cost-effective manner. In this way, they are especially appropriate to treat mine water discharging from abandoned mines. This paper presents geochemical and mineralogical data obtained from a recently constructed passive system in the Jales abandoned mine, north Portugal. It shows the role of fresh ochre-precipitates, formed as waste products from the neutralization process, in the retention of trace elements. Chemical analysis of these waste products revealed strong enrichment factors for metals and arsenic, relative to the water from which they precipitate. The mineralogical study shows that ochre-precipitates are poorly ordered iron-rich material, such as ferrihydrites, that occur as small spherical aggregates (<0.1 μm in diameter). Heating experiments on these precipitates gave rise to hematite and to a crystalline arsenate. This provides evidence for the scavenging of arsenic by means of a precursor arsenic-rich amorphous compound. The results reveal that ochreprecipitates are wastes of environmental concern, which should be taken into account when considering the possibilities for reuse or disposal